EFFECTS OF LIABILITIES OF FOREIGNNESS ON MNCS: AGENCY RELATIONSHIP BETWEEN SUBSIDIARIES & HEADQUARTERS - ATAMAN BERK, GÖKSEL (FUTURE ACAD, 2019)
The current study aimed to examine how the agency relationship is affected between subsidiaries and headquarters of Multinational Companies in case the agent is a citizen of the parent country or host country. The research provides evidence from fourteen individual interviews that agency relations are affected by the parties' nationality differences who are working in headquarter and subsidiary. In addition, it was found that the control mechanisms that should be set up for subsidiaries were different from the control mechanisms used in the local environment because of the institutional and cultural differences between home and host country. In some cultures, it was found that agency relations could be based on trust rather than the sanction power of contracts and that the risk perception of agents could change by the culture. Doing business in the international arena causes problems such as exposure to uncertainties, difficulties in adapting to the environment, and discrimination This is explained theoretically with the Liability of Foreigness. The qualitative research method was used to evaluate the participants' opinions by coding them with the NVIVO program. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Agency theory; liability of foreignness; cultural differences; institutional differences; HCN; PCN; INSTITUTIONAL DISTANCE; CULTURAL DISTANCE; PERFORMANCE; STRATEGY; VALUES; FIRM; DIVERSIFICATION; ECONOMY; MATTERS; PAY